Water balance and expression of heat-shock protein 70 in Codringtonia species: A study within a phylogenetic framework - Kotsakiozi, Panayiota; Parmakelis, Aristeidis; Aggeli, Ioanna-Katerina; Gaitanaki, Catherine; Giokas, Sinos; Valakos, Efstratios D. (Journal of Molluscan StudiesJournal of Molluscan Studies, 2014)
Seasonal differences in the water content of fourCodringtoniaspecies were investigated using specimens collected from the field. In addition, rate of water loss and expression of heat-shock protein 70 (Hsp70) were measured in a laboratory setting with sixCodringtoniaspecies subjected to a short-term heat shock. Using a phylogenetic framework, both the Hsp70 expression levels and the rate of water loss were inves tigated for their correlation with spatial and climatic variables. As indicated by the field-collected samples, during summer aestivation only C. helenaeexhibited a tendency for water loss. During the short-term heat shock the rate of water loss inC. helenaewas also significantly greater. No interspecific differences could be detected in the levels of Hsp70 in the species subjected to short-term heat shock. A singleCodringtoniaspecies seemed to maintain increased Hsp70 protein levels. In the species subjected to short-term heat shock, a positive relationship was found between Hsp70 levels and rate of water loss. On the other hand, the Hsp70 levels under normal conditions showed a negative correlation with altitude and mean summer precipitation of the sampling localities. Thus, species seem to adapt to harsher environmental conditions by maintaining higher levels of Hsp70.